2019
DOI: 10.3390/ijerph16060944
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence Mechanism of CO2 Emissions and Verification of the Environmental Kuznets Curve in China

Abstract: Changes in economic development stage and growth type will lead to variations in the CO2 emissions. Traditional empirical analysis of the variations often only considers the impact of influencing factors on CO2 emissions from a single dimension. Under the background of China’s economy transferring from high-speed growth to high-quality development, this paper comprehensively considers the characteristics of the relevant influencing factors under different development stages and growth rates, and further calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…As for studies on the EKC in China, some find evidence for it (Haisheng et al, 2005;Jalil & Mahmud, 2009;and Jalil & Feridun, 2011); others do not (Du et al, 2012;Wang et al, 2011aWang et al, , 2011b; others find an inverted N-shaped relationship between CO 2 and GDP (Fang et al, 2019;Kang et al, 2016;Onafowora & Owoye, 2014) (Wang et al, 2019); some report the existence of an N trajectory (Dinda et al, 2000;Friedl & Getener, 2003;Lipford & Yandle, 2010;Martinez-Zarzoso & Begonchea-Morancho, 2004;Onafowora & Owoye, 2014). Finally, Riti et al (2017) analyse the relationship between emissions, economic growth and energy consumption in China using a variety of econometric techniques such as ARDL, FMOLS and DOLS that produce similar results providing support for an EKC, but finding a different turning point compared to other studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for studies on the EKC in China, some find evidence for it (Haisheng et al, 2005;Jalil & Mahmud, 2009;and Jalil & Feridun, 2011); others do not (Du et al, 2012;Wang et al, 2011aWang et al, , 2011b; others find an inverted N-shaped relationship between CO 2 and GDP (Fang et al, 2019;Kang et al, 2016;Onafowora & Owoye, 2014) (Wang et al, 2019); some report the existence of an N trajectory (Dinda et al, 2000;Friedl & Getener, 2003;Lipford & Yandle, 2010;Martinez-Zarzoso & Begonchea-Morancho, 2004;Onafowora & Owoye, 2014). Finally, Riti et al (2017) analyse the relationship between emissions, economic growth and energy consumption in China using a variety of econometric techniques such as ARDL, FMOLS and DOLS that produce similar results providing support for an EKC, but finding a different turning point compared to other studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The EKC hypothesis is confirmed in the Sichuan region. Fang et al (2019) analyzed the relationship between EMS, energy intensity, TE, UBZ and GW for the period of 1995-2016 for China. There is an inverted N-shaped relationship between GW and EMS in the Eastern China, Western China and Central China regions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The economy in western China is much less developed than those of northeastern and southern China, so its impact on the environment was smaller (contributions <5% for all economic factors). Many previous studies (Fang, Hao, Wang, & Hao, 2019;Li, Wang, & Zhao, 2016;Rani & Kumar, 2019) showed that the relationship between China's environment and economic development reveals an environmental Kuznets curve, suggesting that environmental degradation initially becomes more serious with increasing economic development in western China. How to successfully move past the inflection point of the environmental Kuznets curve, so that additional development is accompanied by decreasing environmental impacts, will be a tough problem to solve, but it is essential that governments begin trying to solve that problem.…”
Section: Discussionmentioning
confidence: 99%